2020
DOI: 10.1186/s13071-020-04496-2
|View full text |Cite
|
Sign up to set email alerts
|

Giardia duodenalis multi-locus genotypes in dogs with different levels of synanthropism and clinical signs

Abstract: Background In dogs, infections with Giardia duodenalis are mainly caused by assemblages C and D, but also by the potentially zoonotic assemblages A and B. The aims of this study were to assess differences in assemblages (i) between dogs living mainly in close proximity to humans (synanthropic dogs) versus dogs living mainly among other dogs, (ii) between samples of dogs with or without loose stool, and (iii) related to the amount of cysts shedding. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…In accordance with former studies, genotyping results showed that the majority of the Giardia positive samples were allocated to the canine type, consisting of the assemblages C and D (38.4 (43/112) and 35.7% (40/112)), respectively (Johansen et al 2014;Pallant et al 2015;Zhang et al 2017;Sommer et al 2018;Uiterwijk et al 2020). Furthermore, we were able to identify 8% (9/112) of the isolates as the potentially zoonotic assemblage A.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In accordance with former studies, genotyping results showed that the majority of the Giardia positive samples were allocated to the canine type, consisting of the assemblages C and D (38.4 (43/112) and 35.7% (40/112)), respectively (Johansen et al 2014;Pallant et al 2015;Zhang et al 2017;Sommer et al 2018;Uiterwijk et al 2020). Furthermore, we were able to identify 8% (9/112) of the isolates as the potentially zoonotic assemblage A.…”
Section: Discussionsupporting
confidence: 90%
“…Dogs are particularly affected by the canine-specific types C and D, which are responsible for most of the infections in dogs. However, in several studies, assemblages A and more rarely B have also been detected (Ballweber et al 2010;Sotiriadou et al 2013;Sommer et al 2018;Uiterwijk et al 2020). In addition to G. duodenalis, also other endoparasites, such as T. canis, are potentially zoonotic and transmitted via the fecal-oral route by direct contact with the agent or through contaminated water or food (Thompson and Monis 2012;Macpherson 2013;Chen et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These findings may suggest that a number of factors may contribute to the high prevalence of G. duodenalis in this kennel. Overcrowding is considered a favourable factor for the spread of this protozoan parasite [3,8,16]. Effective sanitisation and control measures may also be more difficult to perform in these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Assemblages C and D are canine specific. Assemblages A and B are most frequently found in humans, but they can also infect other animals and are considered potentially zoonotic [5][6][7][8]. Assemblages A and B have been further divided into sub-assemblages (A-I to A-III and B-III, B-IV), some of which are more common in humans and others in animals [2,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation